PEMUKIMAN-PEMUKIMAN KUNO DI DAERAH ALIRAN SUNGAI BATANGHARI - Arif Rahim (Universitas Batanghari Jambi, 2017)
This paper deals with ancient settlements along the Batanghari river basin. region Through the historical and archaeological approach, it can be concluded that the formation of ancient settlements along the watershed (Batanghari) watershed is influenced by the geographical factors, the needs and the interests of the settlers in accordance with the times. Establishment of early settlements in the area of Jambi Hulu has led to the opening of agricultural land in the form of fields, gardens, and paddy fields, and in the next mining is mainly gold. Settlements of Koto Kandis, Muaro Jambi, and Solok Sipin are emerging and emerging settlements driven by their strategic location on international trade routes, supported by many trading commodities in the rural areas traded in these places. The existence of settlements of Padang Rocok / Sungai Lansek, Siguntur and Rambahan, is as a result of the removal of the center of the Malay kingdom that originally resided in Muaro Jambi. Supported by a place that can be reached via the river, and its location close to the production of gold and pepper cause the settlement even developed into a crowded city. The Rantau Panjang and other settlements in Jambi Hulu were formed as a result of the displacement of the Batin and Penghulu from Minangkabau. Especially the Penghulu their arrival was driven by their interest in gold mining and trading. Their arrival in Jambi Hulu has caused the highlands of Jambi to have a strong Minangkabau influence in various aspects such as adat, kinship social system, language, building style, to some extent including aspects of royal governmentKeyword: the ancient settlement on the river